Development of Essential Thinking Test Instrument using the Presseisen Taxonomy on Ecosystem Material for Grade X High School Students - Afandi, Afandi; Yuniarti*, Anisyah; Fadhilah, Azfa; Karolina, Venny; Queiroz, Carla Cristiana (Universitas Syiah Kuala, 2024)
The test instrument is a measuring tool in the assessment process used to obtain information in the form of data on student learning outcomes, both cognitive aspects and thinking skills. The use of test instrument to measure students' thinking skills is still rarely used. This study aims to develop an essential thinking test instrument using the Presseisen taxonomy on valid and reliable ecosystem material. This research uses the Research Development (RD) method with the 3D modified development model combined with the test development stages consisting of 6 stages. Data collection in this research was carried with interviews, tests, and test instrument validation sheets. The analysis included content validity analysis, interrater reliability, and Rasch model analysis. The results showed that all items were valid based on content validity. Interrater reliability has a value of 0.783 with a good category. All items are declared fit, but item number 7 contains bias so it needs to be discarded. Cronbach's alpha has a value of 0.68 in the enough category, person reliability has a value of 0.50 in the weak category, and item reliability has a value of 0.99 in the excellent category. The item difficulty level group consists of 2 very difficult questions, 4 difficult questions, 2 easy questions, and 2 very easy questions. Based on the result of the research, it can be concluded that there are 9 items that are declared valid and reliable for use.